Squamous-cell carcinoma in a female patient suffering from recessive dystrophic epidermolysis bullosa - A. E. Karamova; V. V. Chikin; V. I. Albanova; V. A. Smolyannikova; M. A. Nefedova; E. S. Monchakovskaya (State Scientific Center of Dermatovenereology and Cosmetology, 2017)
The article describes a case of squamous-cell carcinoma in a female patient aged 30 suffering from a rare inherited disease -recessive dystrophic epidermolysis bullosa (RDEB). RDEB is characterized by a high risk of squamous cell carcinoma in young patients. The most frequent form is a highly differentiated form of cancer characterized by an aggressive course with the early development of metastases and fast progression, which is the most frequent cause of death in RDEB patients. The described case of squamous cell carcinoma in a young female RDEB patient emphasizes the role of early tumor diagnostics.